2015
DOI: 10.1590/0100-69912015003005
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for short gastric vessels division during laparoscopic total fundoplication

Abstract: the division of the short gastric vessels is not required routinely, but male gender and grade IV-V esophagitis are independent predictors of the need for section of these vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Although no study has formally implicated division of short gastric vessels as a risk factor for delayed gastric empting, several randomized trials and meta‐analyses have found that routine division of short gastric vessels during laparoscopic fundoplication is associated with higher rates of postprandial bloating22, 23, 24, which may reflect delayed gastric emptying. Despite the rationale that division of short gastric vessels may facilitate the creation of a tension‐free fundoplication and minimize the risk of postoperative dysphagia25, multiple studies26, 27, 28, 29 have demonstrated that this intraoperative manoeuvre does not influence swallowing outcomes after antireflux surgery. Therefore, some surgeons no longer routinely divide the short gastric vessels30, 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…Although no study has formally implicated division of short gastric vessels as a risk factor for delayed gastric empting, several randomized trials and meta‐analyses have found that routine division of short gastric vessels during laparoscopic fundoplication is associated with higher rates of postprandial bloating22, 23, 24, which may reflect delayed gastric emptying. Despite the rationale that division of short gastric vessels may facilitate the creation of a tension‐free fundoplication and minimize the risk of postoperative dysphagia25, multiple studies26, 27, 28, 29 have demonstrated that this intraoperative manoeuvre does not influence swallowing outcomes after antireflux surgery. Therefore, some surgeons no longer routinely divide the short gastric vessels30, 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 , 15 , 19 ] However, multiple randomized prospective studies have shown no impact of this intraoperative modification in the reduction of the above mentioned adverse effect. [ 16 – 18 , 22 , 39 , 40 ] Moreover, a higher incidence of postoperative bloating, re-herniation and longer operating time has been described in patients that underwent the additional modification of the NF. [ 20 , 23 – 25 ] Our results are similar to previous literature showing no difference in postoperative dysphagia rates in patients with and those without division of the SGV (6 groups A + B vs. 5 groups B + C, p = 0.873).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Although it has been claimed that dividing the SGV may minimize the risk of dysphagia [19], different studies failed to demonstrate both short and long-term benefits for patients that underwent this maneuver. [17,18,[20][21][22] Moreover, some trials have reported a higher incidence of abdominal bloating and recurrent hiatal hernia as well as increased operating time including division of the SGV. [23][24][25] Furthermore, added posterior gastropexy aimed to reduce the re-herniation rate and lengthen the intraabdominal esophagus.…”
mentioning
confidence: 99%
“…[19][20][21]23,43 Further randomized controlled trials in which SGVs were divided have shown no impact on PD rates. [44][45][46][47][48][49] How then to interpret our data which, with a statistically significant difference, document a lower incidence of persistent dysphagia in the group of patients undergoing FNF? The difference between NRF and FNF techniques is not limited to the division of SGVs.…”
Section: Discussionmentioning
confidence: 99%